Acceptance of COVID-19 Vaccine Among Refugees in the United States. (November 2021) - Zhang, Mengxi; Gurung, Ashok; Anglewicz, Philip; Subedi, Parangkush; Payton, Colleen; Ali, Ahmed; Ibrahim, Anisa; Haider, Mahri; Hamidi, Navid; Atem, Jacob; Thang, Jenni; Wang, Siqin; et al.
Objective: Little is known about COVID-19 vaccination intentions among refugee communities in the United States. The objective of this study was to measure COVID-19 vaccination intentions among a sample of refugees in the United States and the reasons for their vaccine acceptance or hesitancy. Methods: From December 2020 through January 2021, we emailed or text messaged anonymous online surveys to 12 bilingual leaders in the Afghan, Bhutanese, Somali, South Sudanese, and Burmese refugee communities in the United States. We asked community leaders to complete the survey and share the link with community members who met the inclusion criteria (arrived in the United States as refugees, were aged ≥18, and currently lived in the United States). We compared the characteristics of respondents who intended to receive the COVID-19 vaccine with those of respondents who did not intend to receive the vaccine or were unsure. We then conducted crude and adjusted logistic regression analysis to measure the association between employment as an essential worker and COVID-19 vaccine acceptance. Results: Of 435 respondents, 306 (70.3%) indicated that they planned to receive a COVID-19 vaccine. Being an essential worker (adjusted odds ratio [aOR] = 2.37; 95% CI, 1.44-3.90) and male sex (aOR = 1.87; 95% CI, 1.12-3.12) were significantly associated with higher odds of intending to receive a COVID-19 vaccine. Among respondents who intended to receive a COVID-19 vaccine, wanting to protect themselves (68.6%), family members (65.0%), and other people (54.3%) were the main reasons. Conclusion: Many refugees who responded to the survey, especially those who worked in essential industries, intended to receive a COVID-19 vaccine. Community organizations, health care providers, and public health agencies should work together to ensure that vaccine registration and vaccination sites are accessible to refugees.